We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
219
2
avatar+557 

https://vle.mathswatch.co.uk/images/questions/question2233.png

 

 

winkwinkwink

 Feb 13, 2018
 #1
avatar+101181 
+2

f(x)  = 2x - 3        g(x)  = x^2  + 1

 

a)  f(g(x)  =    2 [ x^2 + 1] - 3    =   2x^2 + 2 - 3   =   2x^2   - 1

 

b)  g(f(x) )  =   [ 2x - 3 ] ^2 + 1  =  4x^2 - 12x + 9 + 1  =  4x^2 - 12x + 10

 

 

cool cool cool

 Feb 13, 2018
 #2
avatar+557 
+2

thank cphill

 

 

winkwinkwink

lynx7  Feb 13, 2018

19 Online Users

avatar
avatar